OPTIMIZATION OF LIPASE PRODUCTION MEDIA PARAMETERS BY A NEWLY ISOLATED BACILLUS LICHENIFORMS KDP FROM OIL MILL SOIL - K . SUJATHA; K. DHANDAYUTHAPANI (International Journal of Pharma and Bio Sciences, 2013)
This experimental research is aimed to meet the industrial demand of lipase enzyme using various supplements along with the optimal physical conditions for enhancing the production. Bacillus licheniforms KDP was used in this study which has been isolated from the oil mill soil. In the present investigation, selenium is used as a media supplement which has not been previously reported as supplement and thus reported by us for the first time. The maximum lipase production (16.23U/ml) was found to be at 60μm/l. Another metal ion, nickel when separately used as supplement to the medium, the maximum production (17.29U/mL) was found to be 80μm/L. The new isolate produced their maximum extracellular lipase at 7.5 (18.69 U/mL) and 45°C (17.36U/mL). The maximum lipase yield 12.43U/mL and15.38U/mL was found to be in the medium containing 0.1mg/l urea and 1mg/l ammonium nitrate respectively. The correlation analyses of all the experiments proved that the physicochemical parameters and the lipase production are interdependent.